Cerebral Dominance for Language in Literates and Illiterates: A Study With Normals - PJ, Kumar (Journal of All India Institute of Speech and Hearing)
Thirty normal right handed literate and thirty normal right handed illiterate adults were administered with a dichotic verbal recall task to determine cerebral dominance for language and to see whether there was any difference in cerebral dominance for language in between these groups. The results indicated a statistically significant difference in cerebral dominance for language for literate and illiterate adults. 13.42 percent of the illiterate subjects and 90 percent of literate subjects showed a left hemisphere dominance for language. Bilateral representation for language was observed in 43.29 percent of illiterates and 10 percent of literates. Right hemisphere dominance for language was observed with 43.29 per cent of the illiterates and it was not exhibited by any of the 30 literate subjects.